Cancer risks from cosmic radiation exposure in flight: A review - Scheibler, Christopher; Toprani, Sneh M.; Mordukhovich, Irina; Schaefer, Matthew; Staffa, Steven; Nagel, Zachary D.; McNeely, Eileen (Frontiers in Public Health, 2022)
Aircrew (consisting of flight attendants, pilots, or flight engineers/navigators) are exposed to cosmic ionizing radiation (CIR) at flight altitude, which originates from solar activity and galactic sources. These exposures accumulate over time and are considerably higher for aircrew compared to the general population, and even higher compared to U.S. radiation workers. Many epidemiological studies on aircrew have observed higher rates of specific cancers compared to the general population. Despite high levels of CIR exposure and elevated rates of cancer in aircrew, a causal link between CIR and cancer has yet to be established. Many challenges still exist in effectively studying this relationship, not the least of which is evaluating CIR exposure separately from the constellation of factors that occur as part of the flight environment. This review concentrates on cancer incidence and mortality observed among aircrew in epidemiologic studies in relation to CIR exposure and limitation trends observed across the literature. The aim of this review is to provide an updated comprehensive summary of the literature that will support future research by identifying epidemiological challenges and highlighting existing increased cancer concerns in an occupation where CIR exposure is anticipated to increase in the future.